2015
DOI: 10.1111/trf.13149
|View full text |Cite
|
Sign up to set email alerts
|

Cost implications of implementation of pathogen‐inactivated platelets

Abstract: BACKGROUNDPathogen inactivation (PI) is a new approach to blood safety that may introduce additional costs. This study identifies costs that could be eliminated, thereby mitigating the financial impact.STUDY DESIGN AND METHODSCost information was obtained from five institutions on tests and procedures (e.g., irradiation) currently performed, that could be eliminated. The impact of increased platelet (PLT) availability due to fewer testing losses, earlier entry into inventory, and fewer outdates with a 7-day sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 39 publications
(44 reference statements)
0
54
0
3
Order By: Relevance
“…The analysis also focused on bacterial contamination only and did not account for potential effects of these approaches on nonbacterial infections. It has been shown that PR can effectively inactivate cytomegalovirus and West Nile virus, among certain other viruses and parasites, and would be expected to eliminate additional costs associated with these tests . Incorporating these additional pathogens would be expected to increase overall costs for the baseline strategy, PORt, and SBC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis also focused on bacterial contamination only and did not account for potential effects of these approaches on nonbacterial infections. It has been shown that PR can effectively inactivate cytomegalovirus and West Nile virus, among certain other viruses and parasites, and would be expected to eliminate additional costs associated with these tests . Incorporating these additional pathogens would be expected to increase overall costs for the baseline strategy, PORt, and SBC.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating these additional pathogens would be expected to increase overall costs for the baseline strategy, PORt, and SBC. However, averted costs from not needing to test for these additional pathogens are small, relative to the cost of PR itself …”
Section: Discussionmentioning
confidence: 99%
“…Numerous papers have analysed the financial cost of implementing PRT . One important aspect of the savings to be made by extending the shelf life of PC to 7 days is the reduction in the number of units discarded due to outdating.…”
Section: Introductionmentioning
confidence: 99%
“…92 The use of PITs will certainly increase the cost of blood products, but this increase in cost is expected to be partially offset by the elimination of the need for irradiation and several types of infectious disease testing (eg, CMV, West Nile virus, and bacterial culture) in pathogen-reduced blood products. 88 Although important questions remain in regard to implementation, PITs will likely end the long-running debate as to whether the addition of CMV-seronegativity to blood products that are already leukoreduced is necessary for optimal prevention of TT-CMV infection. …”
Section: Future Directionsmentioning
confidence: 99%
“…It also decreases the risk of transfusion-associated graft versus host disease through the inactivation of donor leukocytes, possibly obviating the need for irradiation of blood products in at-risk patients. 87,88 Although a licensed pathogen inactivation system is not yet available for red blood cells, the development of such a technology is in progress that uses S-303, a frangible anchor linker effector compound that crosslinks nucleic acids, and glutathione as a quencher to minimize the interaction of S-303 with plasma proteins. 89,90 Adaptation of the riboflavin/ UV method of pathogen inactivation for packed red blood cells and whole blood is also underway.…”
Section: Future Directionsmentioning
confidence: 99%